History text-books of the salesian schools network: requirements and uses (Tempo e Argumento, 2012)
The teaching text book is one of the education tools marked by a confuse set of interests linked to authors, editors, institution managers, among others involved in the process of manufacturing. It is a printed device being a permanent source of research, specially related to the uses did by teachers and students. Thus, in this article, the aim is to present issues about the History text book collection for the high school teaching of the Salesian School Network (RSE in portuguese), in Santa Catarina state: manufacturing context, Salesian net and authors requirements, its utilizations by 5 teachers and 173 high school students. It was observed that the teacher as facilitator of the process teaching-learning, do influence the way students take ownership and produce representations on the text-book a nd the historical knowledge.
Keywords: text-book; history teaching; Salesian Schools Network